A Practical Analgesia Approach to Fragility Hip Fracture: A Single-Center, Retrospective, Cohort Study on Femoral Nerve Block. Issue 4 (April 2019) - Li, Jinlei; Dai, Feng; Chang, Daniel; Harmon, Emily; Ibe, Izuchukwu; Sukumar, Nitin; Halaszynski, Thomas M.; Rubin, Lee E.; O'Connor, Mary I.
Abstract : Objective: To determine whether an effective opioid-sparing pain control modality is desirable for an aging population. Design: Retrospective observational study Setting: Academic medical center Patients: 192 patients with various types of fragility hip fractures Intervention: A single-injection femoral nerve block (FNB) Main outcome measurements: Pain score, opioid consumption Results: We observed statistically significant effects of FNB on visual analogue scale pain score and the rate of opioid consumption diminution in all commonly encountered types of fragility hip fractures. The pain score reduction by FNB in subcapital femoral neck fracture, transcervical femoral neck facture, and intertrochanteric fracture are all statistically significant ( P < 0.0001). There was a statistically more significant pain score reduction in intracapsular fractures than in extracapsular fractures ( P = 0.006). On average, the hip fracture patients required 0.9 and 0.1 mg morphine equivalent/hour before and after FNB block placement. This decrease in opioid consumption when calculated per unit time was statistically significant in subcapital femoral neck fracture, transcervical femoral neck facture, and intertrochanteric fracture ( P < 0.0001). There were no complications related to FNB placement. Conclusions: FNB is a sustainable, safe, and useful analgesic modality for commonly encountered fragility hip fractures. Level of Evidence: Therapeutic Level IV. See Instructions for Authors for a complete description of levels of evidence. Abstract : Supplemental Digital Content is Available in the Text.